(untitled) (XXI Century. Spanish Literature and Culture, 2017)
This work reviews the most noteworthy Spanish novels of 2001 and 2002. The article offers up a review of each novel, taking into account different thematic and formal aspects. Along with authors of large literary trajectories, readers will discover other who, through the sheer quality work alone, will delight them.